Utilization of School Facilities for Literacy and Numeracy Displays - Aidil Fitriansyah; Sherly Marselina; Dina Putriani; Immanuel Pieterson; M. Ikhwanul Fiqri; Reivo Leon Ryadhie; Risky Atikah Tanjung; Rahmilia Syahdilla; Nurul Faoziyah; Nofia Septiani (PT FORMOSA CENDEKIA GLOBAL, 2023)
The Sorek Dua Village KKN student activity program with a qualitative descriptive method was carried out at SDN 006 Sorek Dua. The literacy level of Indonesian students is relatively low. On this basis, reading and writing activities are needed. Students know the unit of length and unit of weight. This certainly increases student learning motivation. Therefore, suggestions for the future are that it is hoped that there will be more recent improvements so that students can know the units of length and units of weight. From the activities carried out at SDN 006 Sorek Dua, it can be concluded that students' ability to understand the concepts of reading, writing and arithmetic lies not only in the school environment but also in the surrounding environment. seem more eager to learn. This certainly increases student learning motivation.